2013
DOI: 10.1519/jsc.0b013e31828c26ec
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Carbohydrate Ingestion During Superimposed Electromyostimulation Exercise in Elite Weightlifters

Abstract: The purpose of this investigation was to test the effects of carbohydrate supplementation on blood parameters and force output during superimposed electromyostimulation (SEMS) single-leg isometric contractions. We hypothesized that carbohydrate ingestion before and during muscle contractions would lead to greater glucose availability and greater total force output for the session. Six elite resistance trained male subjects participated in a randomized, counterbalanced, double-blind study. The subjects were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Another study investigating the role of carbohydrate ingestion during a time to fatigue task found no significant difference (CHO vs. PL) in either the number of successful sets (3.5 6 3.2 vs. 3.5 6 2.7), repetitions (20.4 6 14.9 vs. 19.7 6 13.1), or total work (29.9 6 22.3 kJ vs. 28.6 6 19.5 kJ) performed in the squat exercise (5 repetitions per set) at an intensity of 85% 1RM (12). Possible explanations for the differences observed between the studies of Wax et al (27,28) and Kulik et al (12) may stem from the type of muscular contractions adopted. In particular, isometric contractions at 50% of MVC are expected to partially occlude blood supply (2) and therefore increase the reliance on anaerobic metabolism, specifically through glycolysis.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Another study investigating the role of carbohydrate ingestion during a time to fatigue task found no significant difference (CHO vs. PL) in either the number of successful sets (3.5 6 3.2 vs. 3.5 6 2.7), repetitions (20.4 6 14.9 vs. 19.7 6 13.1), or total work (29.9 6 22.3 kJ vs. 28.6 6 19.5 kJ) performed in the squat exercise (5 repetitions per set) at an intensity of 85% 1RM (12). Possible explanations for the differences observed between the studies of Wax et al (27,28) and Kulik et al (12) may stem from the type of muscular contractions adopted. In particular, isometric contractions at 50% of MVC are expected to partially occlude blood supply (2) and therefore increase the reliance on anaerobic metabolism, specifically through glycolysis.…”
Section: Discussionmentioning
confidence: 96%
“…The studies by Wax et al (27,28), which demonstrated significant improvements in performance with carbohydrate consumption during a time to exhaustion task used a very different protocol to the one adopted in this study. Their protocol consisted of repeated 20-second isometric contractions at 50% MVC followed by 40 seconds of rest until exhaustion.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations